A Systematic Review of Internet Decision-Making Resources for Patients Considering Surgery for Ulcerative Colitis. Issue 8 (13th July 2017) - Baker, Daniel M.; Marshall, Jack H.; Lee, Matthew J.; Jones, Georgina L.; Brown, Steven R.; Lobo, Alan J.
Abstract : Background: Guidance from the Royal College of Surgeons advocates patient use of on-line resources to assist in decision making. Our aim was to assess the quality of on-line resources to facilitate decision making for patients considering surgery for ulcerative colitis (UC). Methods: We undertook a systematic review based on PRISMA guidelines. This was registered on the PROSPERO database (CRD42016047177). We searched Google and repositories using several lay search terms for patient information discussing surgery for UC, published in English. Quality of content on websites was assessed using the validated DISCERN instrument and by minimum standards for decision aids (IPDASi v4.0 checklist). Decision aids were also assessed by the IPDAS checklist. Readability of written content was ascertained using the Flesch–Kincaid score. Results: Our searches identified 175 websites and one decision aid—119 results were excluded at initial screen and 32 were excluded at full text assessment, leaving 25 sources for review. The mean Flesch-Kincaid score for websites was 44.9 (±9.73, range 28.1–61.4), suggesting material was difficult to read. No websites compared surgery to medical management or traded off patient preferences. The median IPDAS score was 5/12 (range 1–7). The median global score based on the DISCERN rating was 1/5 (range 1–5), identifying most websites as poor quality. The decision aid scored 9/12 on the IPDAS checklist, not meeting minimum standards. Conclusions: Available information for patients considering surgery for UC is generally low quality. The development of a new decision aid to support patients considering surgery for UC is recommended.